2013
DOI: 10.1007/s10545-013-9659-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fabry disease in male patients with unexplained left ventricular hypertrophy in primary cardiology practice: prospective Fabry cardiomyopathy screening study (FACSS)

Abstract: The prevalence of FD in our cohort of male patients followed in primary cardiology practice with strictly defined otherwise unexplained LVH was 4 %. We recommend systematic screening for FD in all men older than 30 years with LVH of unknown etiology even in the absence of obvious extracardiac manifestations of FD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 31 publications
1
36
0
3
Order By: Relevance
“…Many screening studies suggest that the identification of FD patients is beneficial as (early) ERT treatment can be initiated [7][8][9][12][13][14][15][16]. We would like to emphasize that this assumption is not sufficiently supported by evidence.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many screening studies suggest that the identification of FD patients is beneficial as (early) ERT treatment can be initiated [7][8][9][12][13][14][15][16]. We would like to emphasize that this assumption is not sufficiently supported by evidence.…”
Section: Discussionmentioning
confidence: 95%
“…Over 670 mutations in the α-galactosidase A (GLA) gene have been described [6], mostly appearing in single families. Since the availability of enzyme replacement therapy (ERT) screening in newborns, high risk populations, as well as individual case finding is increasing [7][8][9][10][11][12][13][14][15][16]. These screening studies report a surprisingly high prevalence of FD in subjects with left ventricular hypertrophy (LVH) (range, 0-12%).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial disorders may present with any combination of organ dysfunctions and at any stage of life and may therefore be seen by nearly any type of specialist physician, although neurologists are perhaps the most likely to be involved given the strong representation of MELAS and CPEO patients in this group. Fabry disease was also diagnosed almost exclusively in adulthood (137 of 147 patients with age at diagnosis data), and given its prevalence in hypertrophic cardiomyopathy, stroke and end-stage renal failure cohorts (Rolfs et al 2005;Gaspar et al 2010;Palecek et al 2014), its importance to adult physicians is noteworthy. It is, however, important to realise that a diagnosis of Fabry disease can be difficult.…”
Section: Age Group At Diagnosismentioning
confidence: 99%
“…However, recent outcome survey analysis revealed that ERT is less efficacious when started after the disease has progressed to such as the occurrence of tissue fibrosis [7]. Considering the requirement of early therapy, neonatal and high-risk screening has been widely performed for an early diagnosis [8], [9], [10], [11], and it has become more and more important to elucidate the basis of Fabry disease and to identify parameters influencing the disease progression.…”
Section: Introductionmentioning
confidence: 99%